Strategies that Contribute to Transform the Perception and Vocational Orientation Towards Engineering Majors in Colombia - Cardona Gil, Jorge Andrés (2025)
The lack of interest in engineering among young people in Colombia calls for an educational strategy that connects theory and practice. Formative assessment and methodologies such as the extended classroom, together with the use of interactive technologies, will enable students to understand the applicability of engineering to everyday problems associated with this profession. In addition, the creation of partnerships between universities and companies will provide professional experiences that will motivate them to see it as a driver of social, environmental, and economic change. Such a shift in education could promote interest in engineering and support technological growth.